The Influence of Attitudes and Work Abilities on Service Quality at the Legal Metrology UPTD of the Trade and Industry Service of Gowa Regency - Damayanti, Damayanti; Sherry Edelia; Natsir Kalla (International Journal of Economic Research and Financial Accounting, 2024)
This research is a type of quantitative research with the aim of knowing and analyzing "The Influence of Attitudes and Work Abilities on Service Quality at the Legal Metrology UPTD of the Gowa Regency Trade and Industry Service". The population in this study is the owners of UTTP equipment (measuring, measuring, weighing, and equipment) who are required to re-calibrate. The total population was 635 UTTP equipment owners using the Slovin formula to determine the sample size, namely 86 respondents. The type of data used in this research is quantitative data obtained from published questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research was the Likert Scale method. Based on the results of research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 27 application regarding the influence of attitudes and work abilities on service quality at the legal metrology uptd of the Gowa district trade and industry service, it can be stated that attitude has a positive but not significant effect on the quality of service at the Legal Metrology UPTD of the Trade and Industry Service of Gowa Regency with a Tcount<Ttable value of 1.351<1.989 so it can be concluded that the hypothesis is rejected. Meanwhile, the ability has a positive and significant effect on the quality of service at the Legal Metrology UPTD of the Trade and Industry Service of Gowa Regency with a Tcount>Ttable value of 9.338>1.989 so it can be concluded that the hypothesis is accepted.